2010
DOI: 10.1016/j.ijdevneu.2010.07.227
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropteridine reductase activity in the brainstem of intrauterine growth‐restricted rats

Abstract: The aim of this study was to determine whether intrauterine growth restriction produces an increase of dihydropteridine reductase activity as a compensatory mechanism that maintains the necessary concentration of cofactor, tetrahydrobiopterin, during accelerated brain serotonin biosynthesis. Intrauterine growth-restricted offspring and controls were used. On days 1, 10, 15 and 21 of life, the brainstem was dissected and l-tryptophan, serotonin, tryptophan-5-hydroxylase and dihydropteridine reductase activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This is supported by a recent study by Piechal and collaborators [28] that conclude that 5-HT does not affect learning and memory. However, other studies reported a significant increase of 5-HT [9,21]. Discrepancies on the effect of 5-HT levels in IUGR animals may be due to the procedure by which IUGR was induced.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is supported by a recent study by Piechal and collaborators [28] that conclude that 5-HT does not affect learning and memory. However, other studies reported a significant increase of 5-HT [9,21]. Discrepancies on the effect of 5-HT levels in IUGR animals may be due to the procedure by which IUGR was induced.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in our study, the IUGR was achievement with the ligation of the placenta vessels which supply to the fetus. Others factors could be explain the differences among studies, such as the cerebral structures included measuring 5-HT changes; here we employed the frontal Ctx, Str and Hipp in comparison with the parietotemporal Ctx [9] or brainstem [21]. Finally, the time of recollection of the samples, while Manjarrez and collaborators used tissues from postnatal days 1, 10, 15 and 21, we only used postnatal day 0.…”
Section: Discussionmentioning
confidence: 99%